KESEIMBANGAN TIGA KEKUATAN JIWA DALAM ETIKA IBNU MISKAWAIH: SOLUSI INTEGRATIF UNTUK PENDIDIKAN KARAKTER ISLAM KONTEMPORER - Amin Nurrohman, Febri; Siregar, Maragustam (EL-MAQRA', 2025)
Contemporary Islamic religious education faces a crisis of fragmentation in student character development, where religious knowledge is not fully actualized in behavior (knowing-doing gap). This research analyzes the concept of Muslim personality formation according to Ibn Miskawayh as an integrative solution to this problem. Through a qualitative approach with in-depth library research, this study examines the balance of three soul powers (Quwwah al-Nāṭiqah, Quwwah al-Ghaḍabiyyah, Quwwah al-Shahwiyyah) within Miskawayh's ethical framework. Findings demonstrate that Miskawayh conceptualizes personality formation as an ongoing pedagogical process, not an instantaneous gift. Miskawayh's three-soul-power balance model offers an integrative solution to the fragmentation of intellectual (IQ), emotional (EQ), and spiritual (SQ) intelligence development. The relevance of Miskawayh's thought to contemporary Islamic education lies in three dimensions: (1) conceptual, providing philosophical foundation to overcome knowing-doing gap; (2) methodological, integrating simultaneous IQ-EQ-SQ development; (3) practical, aligned with the spirit of the Independent Learning curriculum and the goal of forming insan kamil (the complete human). This research contributes to reconstructing classical Islamic ethics as an applicable framework relevant to modern educational challenges, opening opportunities for developing holistic and sustainable Islamic religious education curriculum.